MONETARY CIRCULATION AND BANKS IN THE INTERPRETATION OF THE MAIN ECONOMIC SCHOOLS - Maryna Korol; Ihor Korol; Olena Zayats (Baltic Journal of Economic Studies, 2021)
The topicality of the research lies in the fact that the long-term evolution of financial markets, reinforced by global transformations, has led to the development of convergent processes in banking activities in the presence of significant paradigmatic differences between the major banking systems of the world. The existing peculiarities in the mechanisms and methods of regulation of the banking sector within individual countries have caused drastic changes in views on the nature of the bank and its activities. The traditional view of banks as institutions of financial intermediation, providing the exchange of monetary assets between the owners of savings and borrowers, does not provide for the creation of new money. Instead, proponents of the alternative viewpoint emphasize that in today's world banks finance borrowers mainly through the mechanism of money emission. Both points of view are present to varying degrees in various theoretical and conceptual approaches to understanding the essence of the bank as an institution of financial intermediation. The current economic realities require a detailed study of national banking systems, which largely developed historically, and methodological aspects of their evolution in the context of global transformations. The research subject. In the process of evolution of theoretical and conceptual approaches to the definition of the essence of money, banks, the banking system, the prevailing point of view on this issue has not yet taken a definite form. Nevertheless, the recognition of the effectiveness of banks as a factor of economic growth brings together the positions of competing schools of economic theory. Banks become a factor in the investment process even in the theoretical models of the neoclassical school, which traditionally denies the dependence of economic growth on the money supply. Endogenous growth models recognize the role of banks primarily as a factor in accumulating capital and increasing savings, as well as a mediator between owners of savings and borrowers. Although the Keynesian school of thought initially gave little weight to the functioning of the banking system, neo-Keynesian models have attempted to explain the importance of confidence in the banking system and the need for sound regulatory constraints. The above-mentioned has urged us to carry out this research. The methodological framework of the research is based on an analysis of research on the global debate about the nature of banks in the economy and the architecture of monetary policy. A wide range of theoretical and empirical research methods were used: systematic analysis, synthesis and generalization to formulate conclusions. The aim of the research is to generalize and systematize the evolution of perspectives on money in the interpretations of today’s main economic schools. Conclusion. The findings consist of a conceptualization views' evolution on money, the banking sector in a more open economy to capital flows, and our firm belief that the banking system and the related process of money issuance affect income levels cyclically and over the long term.